REMEDIES FOR THE CRISIS AND CORONAVIRUS-INDUCED INSOLVENCY: WHAT LEGAL "WEAPONS" ARE AVAILABLE TO FIGHT THIS "WAR"? - margherita lazzara (International Journal of Business and Social Science Research, 2020)
This paper aims to define certain rules that may accompany insolvent enterprises and over-indebted households in post-pandemic recovery. At this time, the crucial need to provide entrepreneurs, creditors, debtors, and consumers with certainties cannot be delayed. In the wake of the COVID-19 pandemic, various countries are adopting measures to change the application of their insolvency laws. The Virus was circulating in Italy before spreading to all other European countries, therefore the Italian government had to adopt urgent measures, which drastically impacted insolvency and collective procedures, inter alia. The paper focuses on the legislative provisions adopted by the Italian government as compared to the recent communication of the European Commission of 19 March 2020 ("The new temporary Framework for State aid measures to support the economy in the current COVID-19 outbreak") and to the Directive (U.E.) 2019/1023 on restructuring and insolvency. In light of the foregoing, two solutions will be formulated that may be immediately adopted in support of the debt of enterprises and households to ensure the successful recovery of solvency.